Headache Management in Portugal: Consensus among the Portuguese Headache and Neurology Societies, the Portuguese Association of General and Family Medicine, and MiGRA - Gil-Gouveia, Raquel; Parreira, Elsa; Pavão Martins, Isabel; Luzeiro, Isabel; Marques Pereira, Raúl; Plácido, Madalena; Palavra, Filipe (Acta Médica Portuguesa, 2025)
Headaches are a significant cause of global disability, with migraines ranking second of all conditions in terms of years lived with disability. Most headache patients, including those with migraine, can and should be effectively diagnosed, treated, and managed in primary healthcare settings. This approach not only reduces the disability associated with these conditions but also prevents progression to chronic forms or the development of medication overuse. The establishment of an efficient referral network, involving patient associations and healthcare professionals beyond primary care, is essential to ensure adequate support for more complex cases and to promote population health in a timely and effective manner. These guidelines for diagnosis, treatment, and referral are the result of a consensus among the Portuguese Headache Society, the Portuguese Society of Neurology, the Portuguese Association of Family Medicine, and MiGRA Portugal, the Portuguese association of migraine and headache patients. This document was designed to empower all physicians to contribute effectively to the management of these conditions.